Bridging the gap between data and decisions: A review of process-based models for viticulture. (October 2021) - Knowling, Matthew J.; Bennett, Bree; Ostendorf, Bertram; Westra, Seth; Walker, Rob R.; Pellegrino, Anne; Edwards, Everard J.; Collins, Cassandra; Pagay, Vinay; Grigg, Dylan
Abstract: Context: Effective vineyard decision making at strategic and operational timescales requires consideration of many factors, including vineyard design and management options, exogenous factors that are outside of the decision maker's control such as climate/weather, and desired outcomes such as yield and grape composition attributes. Process-based models enable prediction of vineyard outcomes in response to different decisions and with respect to exogenous factors. Objective: We present a review of process-based models that can simulate both key vineyard outcomes and their sensitivity to decisions and exogenous factors, and highlight how these models can 'bridge the gap' between data and decisions. Methods: We assess the suitability of process-based models to water, canopy and nutrient management contexts using a conceptual systems framework. Results and Conclusions: Currently available process-based models are most advanced in terms of supporting decisions regarding water management, and least advanced regarding nutrient management. They are also better suited to support decisions with respect to yield, compared to grape composition attributes. Significance: This paper provides guidance to modelling practitioners regarding appropriate process-based models for a range of vineyard decision contexts and assists viticulturists and decision makers in understanding how these models can support decisions for improved outcomes. Graphical abstract: Unlabelled Image Highlights: A review of process-based models for decision support in viticulture. Roles and requirements of process-based models for decision support identified using a conceptual systems framework. Assessment of the suitability of process-based models for water, canopy and nutrient management. Address the growing 'data to decisions' gap in viticulture due to under-utilization of process-based models.